The use of telemedicine in primary health care during COVID-19: perceptions from health care professionals - Permana, Iman; Hanifah, Hanifah; Pamungkasih, Wahyu; Mardliyah, Syarifatun; Setyonugroho, Winny; Furqoni, Habib Abda (Intelektual Pustaka Media Utama, 2023)
This research aims to explore the perceptions of health care professionals about the use of telemedicine which took place in Banguntapan 2 primary health care. This study was part of a bigger action research study and was done to obtain an understanding of the telemedicine service as the first step of the diagnosing phase. The respondents are the chief of primary health care, the coordinator of individual health initiatives as well and the coordinator for the appointment program. The selected healthcare professionals were chosen to obtain the telemedicine best-practice in healthcare facilities and to serve as the data triangulation to avoid bias in the answers collected. The result of the interviews revealed four topics: i) the use of telemedicine in minimizing direct contact with the patient; ii) the need to expand the existing system; iii) the utilization of WhatsApp, a popular online platform in the community; and iv) the possibility to merge with the existing online system of national health insurance (JKN) and digital government service (DGS). Some recommendations to improve are to implement a one-stop messaging service, optimization of WhatsApp, and bridge the appointment system to the existing regional DGS.